Neocolonialism through donors aid: Northern-funded transitional justice entrepreneurs and the undermining of an independent victims' agenda in Kenya - Vegh Weis, Valeria (Southernising criminology, 2024)
This chapter examines the atrocities that occurred in Kenya following the disputed 2007 elections and the fragmented and incomplete state response to the crimes. Against this backdrop, and looking at forces from below, the study highlights the wide range of challenges that limit victim empowerment in the aftermath of mass atrocities and how these challenges are largely fueled by neocolonial dynamics that can be found in many other transitional justice scenarios across the Global South. In particular, these challenges involve addressing a fundamental aspect of neocolonial times: the role of donors in funding CSOs/NGOs composed of transitional justice entrepreneurs who often monopolize the process from below and neglect the direct participation of victims. The study is not limited to addressing these challenges but also suggests possible ways forward. In this sense, the chapter asks what would happen if knowledge from the margins were to move to the center of power, that is, if Kenyan victims became the drivers of the process in what can be called a victim-driven approach. The study includes a thorough analysis of secondary sources, as well as 26 interviews conducted through snowball sampling between September 2016 and April 2017, and participant observation at two workshops in Nairobi, two workshops in Mombasa, and three roundtables in Mombasa, Meru, and Kisumu.